Kajian Intrusi Air Laut akibat Backwater di Muara Sungai Citanduy - Hariati, Feril; Taqwa, Fadhila Muhammad Libasut; Qonita, Nadhira Shofa (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2022)
ABSTRACT The Citanduy River Estuary is a coastal area that has the potential to experience seawater intrusion that occurs due to the influence of tides at the river mouth. Seawater intrusion generally has an impact on the need for clean water which is increasingly difficult, because groundwater has been contaminated with seawater. Seawater intrusion that occurs is getting longer and has an impact on agricultural land in the Citanduy watershed. This study aims to predict the length of seawater intrusion due to backwater using HEC-RAS 4.0 software, as well as to analyze the water level profile and backflow that occurs in the Citanduy River. Based on the analysis that has been carried out, the predicted length of seawater intrusion under normal conditions in 2017 and 2050 are 2.57 km and 3.50 km, respectively, the predicted length of seawater intrusion at minimum conditions in 2017 and 2050, respectively. are 2.03 km and 2.57 km, and the predicted length of seawater intrusion at maximum conditions in 2017 and 2050 are 2.57 km and 3.50 km, respectively. Keywords: Seawater Intrusion, Backwater, HEC-RAS 4.0 ABSTRAK Muara Sungai Citanduy merupakan kawasan pesisir yang berpotensi mengalami intrusi air laut yang terjadi akibat pengaruh pasang surut di muara sungai. Intrusi air laut umumnya berdampak pada kebutuhan akan air bersih yang semakin sulit karena air tanah sudah terkontaminasi dengan air laut. Intrusi air laut yang terjadi semakin panjang dan berdampak pada lahan pertanian DAS Citanduy. Penelitian ini bertujuan untuk memprediksi panjang intrusi air laut akibat backwater dengan menggunakan software HEC-RAS 4.0, serta untuk melakukan analisis profil muka air dan arus balik yang terjadi di Sungai Citanduy. Berdasarkan analisis yang telah dilakukan, prediksi panjang intrusi air laut pada kondisi normal di tahun 2017 dan 2050 berturut-turut adalah sebesar 2,57 km dan 3,50 km, prediksi panjang intrusi air laut pada kondisi minimum di tahun 2017 dan 2050 berturut-turut adalah sebesar 2,03 km dan 2,57 km, dan prediksi panjang intrusi air laut pada kondisi maksimum di tahun 2017 dan 2050 berturut-turut adalah sebesar 2,57 km dan 3,50 km. Kata Kunci: Intrusi Air Laut, Backwater, HEC-RAS 4.0